NUMERICAL MODELS OF THE EVOLUTION OF ACCRETIONARY WEDGES AND FOLD-AND-THRUST BELTS USING THE DISTINCT-ELEMENT METHOD - Burbidge D.R.; Braun J. (My University, 2002)
A 2-D numerical model is used to investigate the evolution of accretionary wedges and fold-and-thrust belts. The numerical method is based on the distinct-element method (DEM). Unlike many continuum numerical models, DEM allows localization to occur even after substantial amounts of deformation. The method is used to study the evolution of simple accretionary wedges and thrust belts with a rigid backstop and base. Experiments are done with a large range of coefficients of interelement friction (μ e ) and element-wall friction (μ b ). Two modes of deformation, which depend mainly on μ b, are observed. For the weak base case (low μ b ), the dominant mode is frontal accretion by 'pop-up' structures at or near the toe of the wedge. For the strong base case (high μ b ), uplift is concentrated near the back of the wedge, and is accompanied by underthrusting along a flat-ramp-flat (or 'staircase') thrust fault structure. At intermediate values of μ b, the wedge oscillates between the two modes of deformation. During periods of frontal accretion, normal faulting sometimes occurs in regions where the material has thickened considerably. The transition between the two modes of deformation is found to be a strong function of μ b but a weak function of μ e. A simple explanation of the experimental results is made using the principle of work minimization. Comparisons between the results and some accretionary wedges/fold-and-thrust belts are also made.
Keywords: COLLISION BELTS; CRUSTAL DEFORMATION; FAULTING; LATERAL HETEROGENEITY; NORMAL FAULTING; NUMERICAL TECHNIQUES